Tannhäuser: Poet and Legend With Texts and Translations of his Works - Thomas, J.W (UNC Studies in the Germanic Languages and Literatures, 1974)
To the medievalist, Tannhäuser is the author of ironical and highly original lyrical verse, to the folklorist, the subject of one of Germany's oldest ballads to the musicologist, the composer of the only extant music for a "Tanzleich" and the hero of several operas. J. W. Thomas examines the content and style of Tannhäuser's verse, discusses his sources and his influence on other medieval poets, and gives a history of the ballad material in which he appears. Also included is a diplomatic edition of Tannhäuser's poems, both verse translations of the poems and a version of the ballad, and an extensive bibliography.